Some Speech Aspects of Students' Skills in Improving Oral Speech - Barno Tajimovna Badalova (Zien Journals, 2023)
In this article, the author discusses teaching methods. Methods consist of sequential actions aimed at achieving the goal. Teaching methods are necessary for the development of students' creative abilities, the formation of skills for purposeful independent work, the expansion and deepening of knowledge, the ability to use them in performing specific tasks.
Keywords: method; training; skills